Penguatan Moderasi Beragama melalui Pendekatan Edukatif dan Dialogis: Membangun Sikap Keberagamaan Inklusif pada Peserta Didik SMA - Moh. Dahlan; Moh. Rofid Fikroni (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
The phenomenon of increasing intolerance, exclusivism, and radicalism among youth has become a serious concern. Surveys indicate that educational institutions are not entirely free from radical ideologies. Education should not only transfer knowledge but also shape attitudes, values, and national character through educational and dialogical approaches. The community service employed a qualitative CBPR-PAR approach with active community participation. Data were collected through observation, interviews, documentation, and questionnaires, and then analysed thematically, with triangulation and member checking to ensure validity. The program aimed to strengthen religious moderation among high school students through educational and dialogical methods, enhancing moderate religious literacy, critical awareness of radicalism, and fostering inclusive attitudes. Results showed that the religious moderation intervention increased students’ attitudes by over 30% across nationalism, tolerance, anti-violence, and appreciation of local culture. Dialogical, observational, and reflective approaches promoted empathy, respect for differences, and internalization of diversity. Religious moderation operates simultaneously at cognitive, affective, and social levels, serving as an initial catalyst for inclusive values in students’ daily lives. This service's contribution strengthens religious moderation literacy among high school students, demonstrating the effectiveness of educational-dialogical approaches in shaping inclusive, tolerant attitudes and an appreciation of cultural diversity. Keywords: Religious Moderation,  Dialogical Approach, Tolerance, Inclusivity Fenomena meningkatnya intoleransi, eksklusivisme, dan radikalisme di kalangan generasi muda menjadi perhatian serius. Survei menunjukkan lembaga pendidikan belum sepenuhnya bebas dari pengaruh paham radikal. Pendidikan perlu berperan tidak hanya mentransfer pengetahuan, tetapi juga membentuk sikap, nilai, dan karakter kebangsaan melalui pendekatan edukatif dan dialogis. Pengabdian menggunakan pendekatan kualitatif CBPR-PAR dengan partisipasi aktif masyarakat. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan kuesioner, dianalisis tematik, triangulasi, dan member checking untuk validitas. Kegiatan bertujuan memperkuat moderasi beragama peserta didik SMA melalui pendekatan edukatif dan dialogis, meningkatkan literasi keagamaan moderat, kesadaran kritis terhadap radikalisme, serta menumbuhkan sikap inklusif. Hasil pengabdian menunjukkan bahwa Intervensi moderasi beragama meningkatkan sikap peserta didik >30% pada nasionalisme, toleransi, anti-kekerasan, dan apresiasi budaya lokal. Pendekatan dialogis, observasional, dan reflektif mendorong empati, penghargaan perbedaan, dan internalisasi keragaman. Moderasi beragama bekerja pada level kognitif, afektif, dan sosial, menjadi pemantik awal nilai inklusif dalam kehidupan peserta. Konstribusi pengabdian ini memperkuat literasi moderasi beragama di kalangan peserta didik SMA, menunjukkan efektivitas pendekatan edukatif-dialogis dalam membentuk sikap inklusif, toleran, dan penghargaan terhadap keragaman budaya. Kata kunci: Moderasi Beragama, Pendekatan Dialogis, Toleransi, Inklusivitas